Personal Hygiene Dan Pemeriksaan Angka Kuman Pada Peralatan Makan Pedagang Rujak Di Kawasan Wisata Pantai Natsepa Kecamatan Salahutu - Farha Assagaf; Arfan Ohorella; Arsi Nadila Upuolat (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Personal Hygiene can affect food contamination for several factors including the cleanliness of tableware because the human body can also be a source of pollution including to tableware if it does not maintain cleanliness. Contamination does not occur in food and water sources alone, but food equipment that does not meet health requirements is also a cause. In Indonesia, regulations have been made in the form of Regulation of the Minister of Health of the Republic of Indonesia No.1096 / Menkes / SK / VI / 2011 that for sanitary hygiene requirements for catering services, the number of germs on tableware is 0 (zero). To find out Personal hygiene and bacterial examination of the number of germs on the tableware of salad vendors in the Natsepa Beach Tourism Area, Salahutu District. This type of research is descriptive research with laboratory analysis. The population in this study were 22 salad vendors. The samples used were 5 (five) salad vendors and their cutlery in the Natsepa Beach Tourism Area, Salahutu District. The results of the study have been carried out that the examination of the number of germs on five cutlery plates found in salad vendors I, salad vendors II, salad vendors III, salad vendors IV, and salad vendors V with criteria does not meet the requirements in accordance with Permenkes No. 1096 / Menkes / Per / VI / 2011 which is 0 CFU /cm3. The results showed that five food handlers for personal hygiene did not meet the requirements in the Natsepa Beach Tourism Area. Five samples of cutlery did not meet the health requirements of germ numbers exceeding the threshold value and five food handlers in the Natsepa Beach Tourism Area, Salahutu District had Personal Hygiene that did not meet the requirements.